2023
DOI: 10.1038/s41467-023-39779-6
|View full text |Cite
|
Sign up to set email alerts
|

A supramolecular metalloenzyme possessing robust oxidase-mimetic catalytic function

Abstract: Enzymes fold into unique three-dimensional structures to distribute their reactive amino acid residues, but environmental changes can disrupt their essential folding and lead to irreversible activity loss. The de novo synthesis of enzyme-like active sites is challenging due to the difficulty of replicating the spatial arrangement of functional groups. Here, we present a supramolecular mimetic enzyme formed by self-assembling nucleotides with fluorenylmethyloxycarbonyl (Fmoc)-modified amino acids and copper. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 84 publications
2
21
0
Order By: Relevance
“…We have previously demonstrated the self-assembly of Fmoc-K through fluorenyl-fluorenyl stacking, leading to the formation of ordered structures that facilitate the creation of dicopper sites. 24 In this work, we employed X-ray absorption spectroscopy (XAS) to examine the obtained spectra of the copper-containing complexes. Interestingly, the 1s → 3d transition peak observed in the XAS spectra of the FAD/ Fmoc-K/Cu 2+ complex exhibited remarkable similarity to that of Fmoc-K/Cu 2+ , indicating comparable coordination structures of copper (Figure 2D).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated the self-assembly of Fmoc-K through fluorenyl-fluorenyl stacking, leading to the formation of ordered structures that facilitate the creation of dicopper sites. 24 In this work, we employed X-ray absorption spectroscopy (XAS) to examine the obtained spectra of the copper-containing complexes. Interestingly, the 1s → 3d transition peak observed in the XAS spectra of the FAD/ Fmoc-K/Cu 2+ complex exhibited remarkable similarity to that of Fmoc-K/Cu 2+ , indicating comparable coordination structures of copper (Figure 2D).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Recent studies have shown that the self-assembly of nucleotides with amino acid−based amphiphile aggregates can create a catechol oxidase-like coordination sphere for copper ions. 24 In these studies, the heterogeneous components that comprise the supramolecular catalysts' scaffolds act synergistically in cofactor activation (hemin or Cu 2+ ). However, they do not have well-defined interactions like those in natural multimeric systems, leading to reduced cooperation between the components and poorly resolved active site structures.…”
Section: ■ Introductionmentioning
confidence: 99%
“…21 Such aggregation of Fmoc-K also resulted in the formation of an unsaturated dicopper site. 16 The addition of ssDNA or dsDNA did not alter the fluorescence spectra of Fmoc-K (Fig. 3a and Fig.…”
mentioning
confidence: 90%
“…, Fmoc-lysine (Fmoc-K), Fmoc-histidine (Fmoc-H), Fmoc-arginine (Fmoc-R)) can self-assemble through aromatic stacking of the fluorenyl moiety, to create a catechol oxidase-mimetic coordination sphere for dicopper sites. 16 The introduction of nucleotides, such as guanosine monophosphate, can significantly enhance the activity of Fmoc-amino acids/Cu 2+ . This improvement is attributed to the role of the nitrogen atoms present in the nucleobases, which effectively modify the catalytic microenvironment of copper.…”
mentioning
confidence: 99%
“…Metal-based inorganic material are essential catalytic and structural elements of some (metallo)enzymes. 6 In the field of medicinal chemistry, metal complexes have been used as potential therapeutic agents for treating various kind of diseases. 7 They can inhibit or increase their expression level and activity through conformational changes.…”
Section: Introductionmentioning
confidence: 99%